Optimizing the Management of Uncomplicated Gram-Negative Bloodstream Infections: Consensus Guidance Using a Modified Delphi Process. (11th October 2021) - Heil, Emily L; Bork, Jacqueline T; Abbo, Lilian M; Barlam, Tamar F; Cosgrove, Sara E; Davis, Angelina; Ha, David R; Jenkins, Timothy C; Kaye, Keith S; Lewis, James S; Ortwine, Jessica K; Pogue, Jason M; et al.
Abstract: Background: Guidance on the recommended durations of antibiotic therapy, the use of oral antibiotic therapy, and the need for repeat blood cultures remain incomplete for gram-negative bloodstream infections. We convened a panel of infectious diseases specialists to develop a consensus definition of uncomplicated gram-negative bloodstream infections to assist clinicians with management decisions. Methods: Panelists, who were all blinded to the identity of other members of the panel, used a modified Delphi technique to develop a list of statements describing preferred management approaches for uncomplicated gram-negative bloodstream infections. Panelists provided level of agreement and feedback on consensus statements generated and refined them from the first round of open-ended questions through 3 subsequent rounds. Results: Thirteen infectious diseases specialists (7 physicians and 6 pharmacists) from across the United States participated in the consensus process. A definition of uncomplicated gram-negative bloodstream infection was developed. Considerations cited by panelists in determining if a bloodstream infection was uncomplicated included host immune status, response to therapy, organism identified, source of the bacteremia, and source control measures. For patients meeting this definition, panelists largely agreed that a duration of therapy of 7 days, transitioning to oral antibiotic therapy, and forgoing repeat blood cultures, was reasonable. Conclusions: In the absence of professional guidelines for the management of uncomplicated gram-negative bloodstream infections, the consensus statements developed by a panel of infectious diseases specialists can provide guidance to practitioners for a common clinical scenario.